Development of an anatomically correct mouse phantom for dosimetry measurement in small animal radiotherapy research. (21st June 2019) - Soultanidis, George; Subiel, Anna; Renard, Isaline; Reinhart, Anna Merle; Green, Victoria L; Oelfke, Uwe; Archibald, Stephen J; Greenman, John; Tulk, Amanda; Walker, Adrian; Schettino, Giuseppe; Cawthorne, Christopher J
Abstract: Significant improvements in radiotherapy are likely to come from biological rather than technical optimization, for example increasing tumour radiosensitivity via combination with targeted therapies. Such paradigms must first be evaluated in preclinical models for efficacy, and recent advances in small animal radiotherapy research platforms allow advanced irradiation protocols, similar to those used clinically, to be carried out in orthotopic models. Dose assessment in such systems is complex however, and a lack of established tools and methodologies for traceable and accurate dosimetry is currently limiting the capabilities of such platforms and slowing the clinical uptake of new approaches. Here we report the creation of an anatomically correct phantom, fabricated from materials with tissue-equivalent electron density, into which dosimetry detectors can be incorporated for measurement as part of quality control (QC). The phantom also allows training in preclinical radiotherapy planning and cross-institution validation of dose delivery protocols for small animal radiotherapy platforms without the need to sacrifice animals, with high reproducibility. Mouse CT data was acquired and segmented into soft tissue, bone and lung. The skeleton was fabricated using 3D printing, whilst lung was created using computer numerical control (CNC) milling. Skeleton and lung were then set into a surface-rendered mould and soft tissue material added to create a whole-body phantom. Materials for fabrication were characterized for atomic composition and attenuation for x-ray energies typically found in small animal irradiators. Finally cores were CNC milled to allow intracranial incorporation of bespoke detectors (alanine pellets) for dosimetry measurement.